“ROUTE” STEMS IN THE SUBSTRATE TOPONYMY OF BELOZERYE: AREAL AND ETHNO-LINGUISTIC RELATIONS - Анна Андреевна Макарова (Anna A. Makarova) (Вестник Пермского университета. Российская и зарубежная филология, 2018)
The article discusses the stems with the meaning ‘isthmus, portage’, ‘way, road’, regularly repeating in the substrate toponymy of Belozerye and marking the ways for movement. The study seeks to identify the corpus of toponymic stems with the specified semantics; to establish motivation; to interpret their geographical distribution and determine the most probable ethno-linguistic affiliation. The aim of the study is to clarify the ethno-linguistic characteristics of the substrate toponymy of Belozerye. The source of the material is the data from the files of the Toponymic Expedition of the Ural Federal University (Ekaterinburg) and the Catalog of toponyms of the Institute of Language, Literature and History of the Karelian Research Centre of the Russian Academy of Sciences (Petrozavodsk). In the analytical part of the article, the author proposes stratification of the considered toponymic stems in terms of their origin. The author carries out a directed search for parallels – toponyms with the same stem, which is done on the basis of dictionaries of the Veps, Karelian, Finnish, Sami and Mari languages, as well as with the involvement of already published studies on the toponymy of the Russian North and adjacent regions (Republic of Karelia, Finland, Leningrad Region). Using the areal-typological method, the author analyzes the stems of proto-Uralic (*ukti, *taj-), Finnic (matk, ura), Western Finnic (rata, polku) and Mari (korno) origins. Based on the areal relations of the identified geographical names and the spread of the stems in the Finno-Ugric languages (Finnic, Saami, Volga-Finnic), as well as the availability of the appropriate lexemes in the dialects of the Russian language, the author draws some conclusions about the specific features of the substrate toponymy of Belozerye. Several cases of semantic calquing are noted: lake Ukhtomyarskoe and river Matterka (Ukhtoma), river Matkinets and river Kornoma; lake Volotskoye and river Ukhtomka; as well as cases of ”assemblage” of ”route” toponyms on watersheds ...